Systematic Educational Research Planning - Muhammad Raihan Putra Damar Septian; Bayu Bambang Nurfauji; Risma Sri Wahyuni; Hilmi Abdul Halim; Tedi Priatna (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze educational research planning systematic through a aqualitative approach based on library research by analyzing key concepts and prinsiples of research methodology from various academic sources. Data analysis was carried out using content analysis techniques the stages of classification, desription, synthesis, and then drawing conclusions. The results of the discussion grouped three main pillars of planning: firs, problem formulation that must meet empirical, specific, and relevant criteria; second is the function of theory and conceptual foundation as an academic foundation for building a framework of thought and finding research gaps or gaps; and finaly, the hypothesis formulation technique as a rational and empitically tested temporary solution or answer. It was concluded that systematic planning, starting from defining the problem to proposing a hypothesis supported by theory, is an absolite prerequisite for ensuring the validity, focus and contribution of educational research.